Effects of specific dual task training on change of direction ability, cognitive flexibility, and inhibition in young soccer players - Baccouch, R.; Borji, R.; Ayed, H.; Sahli, S.; Zammit, Y.; Rebai, H. (Perceptual and Motor Skills, 2024)
In the current study we aimed to investigate the effect of specific dual task training (SDTT) compared to conventional soccer training (CST) on motor and cognitive performances in U13 elite soccer players. Twenty-four young soccer players (all males) participated in this study. We measured their change of direction ability (CODA) and cognitive performances (cognitive flexibility and inhibition) before and after four weeks in either the SDTT group or the CST group. We administered the Trail-Making Test (TMT) to evaluate cognitive flexibility and the Stroop test to evaluate cognitive inhibition. We assessed CODA using the t test (TT). After training, CODA (p < .001), cognitive flexibility (p < .001), and inhibition (p < .001) were improved only in the SDTT group. These results suggest that SDTT seems more suitable than CST to optimally improve both CODA and cognitive performances in U13 elite soccer players.